38 Efficacy of DC cardioversion for atrial fibrillation: a large retrospective observational study. (May 2019) - Carpenter, Alexander; Graby, John; Medland, Rachael; Brown, Stewart; Sowerby, Claire; Priestman, Louise; Dayer, Mark; Furniss, Guy
Abstract : Introduction: The evidence base for rhythm control strategies in atrial fibrillation (AF) remain contentious. Synchronised DC cardioversion (DCCV) is a simple and accessible treatment option in many centres. However, there is little data to support its use as a long-term strategy or data regarding which groups benefit most from this strategy. Methods: We collected AF cardioversion cases across a six-year period at a busy district general hospital with a nurse-led cardioversion service. Demographic, echocardiographic and procedural data were collected, as were safety and AF outcomes at 6 and 12 months. Patients with incomplete data were excluded from the analysis. Statistical analysis was undertaken using the Fischer's exact T-test. Results: 550 cardioversion cases were included in the analysis with a median age of 67 (range 28–95). 163 (30%) of patients were obese (BMI ≥30). The mean CHA2DS2-VASc was 2.3. 342 (62%) of DCCV were for persistent AF, the remainder (208; 38%) longstanding (AF duration >1 year) persistent. 162 (29%) had an unknown duration of AF due to an incidental diagnosis. 483 (88%) were on AV-nodal blocking and 103 (19%) on anti-arrhythmic medication (flecainide, sotalol or amiodarone). 516 (94%) of DCCVs were acutely successful with a complication rate of 2% (n=13), most commonly symptomatic bradycardia requiring temporary transcutaneous (n=2) or percussion pacing (n=6) with no acute strokes. At 1 year 5 (0.9%) had had a stroke/transient ischaemic attack and 9 (1.6%) died. 179/478 (37%) of patients were free from AF at 6 months, with 100/412 (24%) free from AF at 1 year. 89 (16%) of patients were referred for further cardioversion and 144 (26%) referred for catheter ablation. There was no statistically significant effect of patient age, obesity, left ventricular (LV) impairment, or left atrial (LA) dilatation on 6-month outcomes. However, AF duration <1 year did correlate with statistically significant improvement in 6 month freedom from AF (41% vs 31%, p=0.03). In those with moderate/severe LV impairment, anti-arrhythmic use significantly improved 6-month outcomes (70% vs 40%, p=0.01). However, no such effect was seen between moderate/severely dilated and non-dilated LA. Conclusion: DCCV for AF remains a safe procedure with good acute success rates. However, within 6 months the majority of patients will have reverted to AF. AF duration of less than 1 year is associated with an improved 6-month success rate, as does antiarrhythmic use in those with impaired LV function. In selected patients, DCCV remains a useful tool as a 'trial of sinus rhythm' to establish potential symptomatic benefits from pursuing a rhythm control strategy. Conflict of Interest: Nil